2010
DOI: 10.3899/jrheum.090048
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus, a Calcineurin Inhibitor, Overcomes Treatment Unresponsiveness Mediated by P-glycoprotein on Lymphocytes in Refractory Rheumatoid Arthritis

Abstract: ABSTRACT. Objective. Tacrolimus, a calcineurin inhibitor, is used for treatment of rheumatoid arthritis (RA). It also inhibits functions of P-glycoprotein, which is involved in drug resistance. We examined the mechanisms of early response to 2-week tacrolimus treatment in patients with RA. Methods. One hundred thirteen patients with refractory RA despite at least 3 antirheumatic agents, including methotrexate, were treated with tacrolimus (1.5-3 mg/day) and the response was assessed at 2 weeks. Expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…In our clinical trial, we experienced refractory patients with high disease activity who were treated with lowdose cyclosporine or tacrolimus and showed significant improvement of clinical features within two weeks, which was not accompanied by falls in Pgp expression levels on lymphocytes [30] . One representative case was a 56yearold woman with Pgpoverexpressing lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…In our clinical trial, we experienced refractory patients with high disease activity who were treated with lowdose cyclosporine or tacrolimus and showed significant improvement of clinical features within two weeks, which was not accompanied by falls in Pgp expression levels on lymphocytes [30] . One representative case was a 56yearold woman with Pgpoverexpressing lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…*p \ 0.05, compared with 0 months Rheumatol Int including MTX and glucocorticoids. Previous studies have revealed that the high P-gp expression by the lymphocytes of RA patient is related to a high DAS score and that TAC and cyclosporine-A overcome the treatment unresponsiveness mediated by P-gp [20][21][22]. Therefore, we believe that, because patients with a high DAS score despite MTX treatment had the possibility of having high P-gp activity, the patients with higher DAS scores would experience a better treatment response to TAC, including improvement of intracellular accumulation of concurrent drugs, such as MTX.…”
Section: Discussionmentioning
confidence: 99%
“…The other mechanism of tacrolimus depends on its inhibitory effects on Pglycoprotein, which accelerate to excrete concomitant drugs from the inside of cells. Therefore, tacrolimus can restore the intracellular therapeutic levels of corticosteroids, thereby leading to the improvement of LN (29). A previous study showed that treatment with angiotensin receptor blockers reduces proteinuria in conjunction with immunosuppressive therapy in patients with LN (30).…”
Section: Discussionmentioning
confidence: 99%